The devil is in the detail: deception and consistency over repeated interviews - Hudson, Charlotte A. (Psychology, crime & law, 2019)
Research indicates that truthful statements typically contain more details than fabricated statements, and that truth tellers are no more consistent than liars over multiple interviews. In this experiment, we examine the impact of (i) multiple interviewers and (ii) reverse order recall on liars’ and truth tellers’ consistency and amount of reported detail over repeated recall attempts. Participants either took part in a mock crime (lying condition) or an innocent event (truth telling condition) which they were subsequently interviewed about in two separate interview phases. Truth tellers provided more details overall, and more reminiscent details than liars. There were no differences between veracity groups for the number of omissions made or repetitions reported. Despite the popular belief that inconsistency is a cue to deception, we found little support for the notion that consistency (or lack of consistency) offers a diagnostic cue to deception. We found little evidence that switching interviewer or recalling in reverse order induced inconsistencies in liars. In fact, due to the number of reminiscent details in truth tellers’ accounts, our findings suggest that accounts provided by liars tend to be slightly more consistent than those provided by truth tellers. Materials for this paper can be found at osf.io/hgvmk/.